Ethnic identity of young Malaysian adolescents in Sarawak - Ting, Su Hie; Ling, Teck Yee (INSTITUTE FOR YOUTH RESEARCH MALAYSIA, 2011)
The study examined the ethnic identity of young Malaysian adolescents living in Sarawak from the aspects of their identification with their own ethnic group and their tolerance of ethnic diversity. The ethnic groups focused on were the Malay, Chinese and Indigenous groups of Sarawak. The development of ethnic identity of the adolescents was measured by means of Phinney’s (1992) multigroup ethnic identity measure. The data for the study were obtained from 1181 participants aged 13 to 17 in three urban and three rural localities in Sarawak. The results showed positive ethnic identity development for the group of adolescents under study, with frequent reports of affective behaviour towards their own ethnic group. However, this was not backed by up an equally strong display of ethnic behaviour such as using the ethnic language, practicing the life style of the ethnic group and interaction with members of the same ethnic group. A comparison by ethnic group revealed that the Indigenous participants had the strongest affiliation with their ethnic group, followed by the Malay participants, and the lowest was shown by the Chinese participants. The results suggest that the close proximity in social space for the adolescent Malaysians generates the conditions for them to construct notions of an ethnic identity that is hinged on the distinctiveness of their own ethnic group and interlaced with cultural elements of other ethnic groups.